Pengaruh infeksi soil transmitted helminth (STH) terhadap daya ingat dan koordinasi visual-motorik dalam fungsi kognitif anak-anak sdn 1 sulangai, Kabupaten Badung, dan SDN 1 Blandingan, Kabupaten Bangli, Bali - Pratiwi, Ida Ayu Ide Larassanthi; Swastika, I Kadek; Sudarmaja, I Made (E-Jurnal Medika Udayana, 2018)
Soil Transmitted Helminth (STH) Infection, indirectly affect cognitive function in children who have a higher susceptibility compared with other age groups. Lack of food intake, indigestion, malabsorption, and poor growth rates are often found in children with ascariasis and trichuriasis. Therefore, helminth infection can cause a decrease in cognitive development of memory and visual-motoric coordination, thus preventing the child from reaching their proper potential growth. The aim of this study is to measure and prove the effect between helminth infection and cognitive function. The study design was cross-sectional observational analysis with 273 respondents were school children of SDN 1 Sulangai, Badung and SDN 1 Blandingan, Bangli. It was applied by using Kato Katz technique in stool sample examination and Wechsler Intelligence Scale for Children III (WISC III) as memory and visual-motoric test. After adjusting for the potential confounder age, sex, and socioeconomic status (SES), obtained children with positive and negative of helminth infection each counted 12 people. Analysis of data through SPSS gradually using Paired Sample T-test with p value of 0.074 and 0.851 (p> 0.05) to know the mean difference of pre-test with post-test of cognitive function. The Independent Sample T-test with p value results on pre-test and post-test cognitive function in relation to the occurrence of helminth infection respectively were 0.922; 1.000; 0.722; and 0.328 (p> 0.05). It was concluded that there was no effect of helminth infection toward cognitive function specifically memory and visual-motoric coordination in SDN 1 Sulangai, Badung and SDN 1 Blandingan, Bangli. Keywords: Soil Transmitted Helminth (STH), cognitive function, school children